Effect of titanium dioxide on the UV‐C ageing behavior of silicone rubber. Issue 14 (11th December 2017) - Zhang, Hui; Yang, Hao; Shentu, Baoqing; Chen, Songjun; Chen, Ming
ABSTRACT: The ultraviolet (UV)‐C ageing behavior of silicone rubber (SiR) incorporated with titanium dioxide nanoparticles (nano‐TiO2 ) was studied under UV‐C radiation. The SiR incorporated with nano‐TiO2 displayed excellent physical properties when exposed to UV‐C radiation. With the increase of the ageing time, the SiR with nano‐TiO2 showed no significant change in crosslinking density and Shore A hardness. Moreover, compared with the SiR without nano‐TiO2, the SiR incorporated with nano‐TiO2 also exhibited high retention ratio in tensile properties, especially elongation at break. It was found that nano‐TiO2 was a good ultraviolet light stabilizer during the UV ageing process of SiR and the optimum content of nano‐TiO2 was 2 phr. The results of Fourier transform infrared spectroscopy and X‐ray photoelectron spectroscopy showed the appearance of OH and CO and the decrease of the intensity of SiC2 O2 in SiR samples during the process of UV‐C ageing. Based on these results, a possible UV ageing mechanism of SiR could be proposed. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46099. Abstract :